Political Legitimacy and Representation in Al-Mawardi’s Political Thought: Reinterpreting the Concept of Ahl al-Ḥall wa al-‘Aqd in Modern Representative Democracy - Ananda, Yudha Tama Dwi; Qohar, Abd.; Yudha (Scopus ID: 57205266060), Gesit (Analisis: Jurnal Studi Keislaman, 2026)
Political legitimacy and representation have become fundamental issues in contemporary democracy, particularly amid declining public trust, weakening political accountability, and rising demands for higher-quality representative institutions. Within this context, Al-Mawardi’s political thought offers a normative perspective that remains highly relevant, although it has generally been interpreted as a model of classical Islamic political institutions. This study aims to examine the concepts of political legitimacy and representation in Al-Mawardi’s political thought and to reinterpret the concept of Ahl al-Hall wa al-‘Aqd. Employing a qualitative library research approach, the study analyzes Al-Aḥkam al-Sulṭaniyyah as the primary source and places it in dialogue with contemporary theories of political legitimacy and representation. The findings reveal that political legitimacy in Al-Mawardi’s thought is constructed through the integration of Islamic legal principles, leadership competence, and public recognition. At the same time, Ahl al-Hall wa al-‘Aqd serves as a representative mechanism grounded in competence, integrity, accountability, and the pursuit of the common good (maslaḥah). The novelty of this study lies in reinterpreting Ahl al-Hall wa al-‘Aqd as an ethical framework of political representation and reconstructing Al-Mawardi’s political thought through the concepts of normative-representative legitimacy and normative-meritocratic representation. These conceptual contributions enrich both Islamic political thought and contemporary theories of representative democracy.